(Dis)Connecting Through COVID-19: Experiences of Older Persons in the Context of a Volunteer–Client Relationship. Issue 4 (20th December 2021) - Bruce, Paxton; Pesut, Barbara; Dunlop, Rowena; Puurveen, Gloria; Duggleby, Wendy
Abstract: The coronavirus (COVID-19) pandemic and mandated physical distancing requirements significantly impacted volunteer programs for older persons with many long-standing programs either ceasing altogether or pivoting to connecting through virtual technologies. In this study, we collected qualitative interview data from 23 clients and 33 volunteers to investigate their experiences during the COVID-19 pandemic and the effects on the volunteer–client relationship. Three themes were identified: pandemic emotions, negotiating social interactions, and growing through the COVID-19 pandemic. These findings provide important insights into the experiences of hospice organizations and their volunteers and clients during the COVID 19 pandemic, further highlighting the importance of acknowledging both older persons' vulnerability and their resilience, of building in compassionate community approaches to care, and of finding innovative ways to foster volunteer–client relationships during times when physical visiting is not possible.